A Morphometric analysis of long-tongued nectar bat (pteropodidae : Macroglossus minimus) in Sabah and Sarawak - W. Gom, Elina (University Malaysia Sarawak, UNIMAS., 2013)
A study on the morphometric variations of Macroglossus minimus was carried out to analyse the morphological variation among four populations from Sabah and Sarawak and also to determine the best character that differentiate this species between populations. M. minimus were morphologically analysed where 32 characters of body, skull and dental measurements were recorded. Univariate analysis,Discriminant Function Analysis (DFA) and cluster analysis were done separately on three categories of characters: external characters, internal characters and pooled external and internal characters. Univariate Analysis shows sexual dimorphism by three internal characters namely, zygomatic width (ZW), canine tooth basal width (C1BW) and breadth across both canines outside surface (C1C1B) respectively. DFA shows that the most effective way to identify this bat is by pooling both external and internal characters together and the best characters to differentiate M. minimus between populations were fifth digit metacarpal length (D5MCL), forearm (FA), great skull length (GSL) and dental length (DL).